SERVICE QUALITY DEVELOPMENT STRATEGY THROUGH BANKING DIGITALIZATION AT PT.BPR TANAOBA LAIS MANEKAT - Ritha Lidia Frare; Rohmawati Kusumaningtias (Publikasi Indonesia, 2024)
This research aims to explore strategies for developing the quality of banking services through digitalization in PT. BPR Tanaoba Lais Manekat (TLM). In the era of Industry 4.0, digital transformation has become an urgent need to improve service efficiency and meet customer needs. The research method used is a descriptive qualitative approach with a case study on BPR TLM in Kupang, East Nusa Tenggara. Data was collected through interviews, observations, and documentation. The results of the study show that BPR TLM has utilized digital technology in the development of its services, such as the use of social media for promotion and implementation plans of self-service service systems, including mobile banking and internet banking. However, there are obstacles in the form of a lack of competent human resources in managing social media and digital infrastructure that are not optimal. This transformation is expected to improve service quality, customer loyalty, and the bank's competitiveness.